Visible light driven photocatalytic hydrogen evolution and photophysical properties of Bi3+ doped NaTaO3 - Kanhere, Pushkar D. (2013)
Visible light active Bismuth doped NaTaO3 powders were synthesized by the conventional solid state route for different Bi concentrations (2.5%, 5.0%, and 7.5% by moles). The optical properties of the doped samples were tuned by changing the molar ratio of Na and Ta in the initial reactants. The doped samples prepared with Na/Ta ratio close to unity (1.01–1.03) resulted in the highest band gap narrowing compared to the other synthesis conditions. It was shown that the photocatalytic hydrogen evolution occurred from these samples under the visible light irradiation (λ > 390 nm) after loading of appropriate amount of platinum co-catalyst. The other synthesis conditions (Na/Ta = 1/1−x; x = 0.025, 0.05, 0.075 and Ta/Na = 1/1−x; x = 0.025, 0.05, 0.075; x is bismuth content) were not useful for the photocatalytic hydrogen evolution. The structural characterization suggested that the samples prepared with Na/Ta ratio close to unity, contain Bi ions located at both Na and Ta sites in the lattice. The Mott–Schottky plots revealed that the flat band potential of the pristine NaTaO3 is highly negative to the H2/H2O reduction potential (−1.19 eV vs. SCE, pH = 7) and for all Bi doped NaTaO3 samples, the flat band potential was sufficient for the hydrogen generation.